Comprehensive Time-Series Analysis of the Gene Expression Profile in a Susceptible Cultivar of Tree Tomato (Solanum betaceum) During the Infection of Phytophthora betacei - Bautista, Daniel; Guayazan-Palacios, Natalia; Buitrago, Maria Camila; Cardenas, Martha; Botero, David; Duitama, Jorge; Bernal, Adriana J.; Restrepo, Silvia (Frontiers in Plant Science, 2021)
Solanum betaceum is a tree from the Andean region bearing edible fruits, considered an exotic export. Although there has been renewed interest in its commercialization, sustainability and disease management have been limiting factors. Phytophthora betacei is a recently described species that causes late blight in S. betaceum. There is no general study of the response of S. betaceum, particularly, in the changes in expression of pathogenesis-related genes. In this manuscript we present a comprehensive RNA-seq time-series study of the plant response to the infection of P. betacei. Following six timepoints of infection, the differentially expressed genes involved in the defense by the plant were contextualized in a sequential manner. We documented 5628 differentially expressed genes (DEGs) across all time-points. From 6 to 24 hours post inoculation, we highlighted DEGs involved in the recognition of the pathogen by the likely activation of pattern triggered immunity (PTI) genes. We also describe the possible effect of the pathogen effectors in the host during the effector-triggered response. Finally, we reveal genes related to the susceptible outcome of the interaction caused by the onset of necrotrophy and the sharp transcriptional changes as a response to the pathogen. This is the first report of the transcriptome of the tree tomato in response to the newly described pathogen P. betacei.